2021
DOI: 10.1038/s41396-021-01134-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to an amoeba host drives selection of virulence-associated traits in Vibrio cholerae

Abstract: Predation by heterotrophic protists drives the emergence of adaptive traits in bacteria, and often these traits lead to altered interactions with hosts and persistence in the environment. Here we studied adaptation of the cholera pathogen, Vibrio cholerae during long-term co-incubation with the protist host, Acanthamoeba castellanii. We determined phenotypic and genotypic changes associated with long-term intra-amoebal host adaptation and how this impacts pathogen survival and fitness. We showed that adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…These evolved defense mechanisms can function as virulence factors that are necessary for bacterial survival in macrophages and persistence in the environment . Thus, adaptation to protist hosts is widely recognized as training grounds for bacterial pathogenicity and the emergence of human pathogens from environmental reservoirs. , Among defense mechanisms, bacterial Cu resistance is an essential virulence determinant for bacterial pathogenicity, enabling bacteria to detoxify Cu toxicity during infection and survive in mammalian hosts . Some studies also demonstrated that Cu resistance facilitates tissue colonization, infection, and inflammation for a variety of bacterial pathogens, such as E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These evolved defense mechanisms can function as virulence factors that are necessary for bacterial survival in macrophages and persistence in the environment . Thus, adaptation to protist hosts is widely recognized as training grounds for bacterial pathogenicity and the emergence of human pathogens from environmental reservoirs. , Among defense mechanisms, bacterial Cu resistance is an essential virulence determinant for bacterial pathogenicity, enabling bacteria to detoxify Cu toxicity during infection and survive in mammalian hosts . Some studies also demonstrated that Cu resistance facilitates tissue colonization, infection, and inflammation for a variety of bacterial pathogens, such as E.…”
Section: Discussionmentioning
confidence: 99%
“…74 Thus, adaptation to protist hosts is widely recognized as training grounds for bacterial pathogenicity and the emergence of human pathogens from environmental reservoirs. 75,76 Among defense mechanisms, bacterial Cu resistance is an essential virulence determinant for bacterial pathogenicity, enabling bacteria to detoxify Cu toxicity during infection and survive in mammalian hosts. 14 Some studies also demonstrated that Cu resistance facilitates tissue colonization, infection, and inflammation for a variety of bacterial pathogens, such as E. coli, Mycobacterium tuberculosis, Acinetobacter baumannii, Listeria monocytogenes, P. aeruginosa, and Staphylococcus aureus.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These are secretion P-type DNA transfer genes that aid in substrate secretion through a cell envelope spanning structure, preventing bacterial cell lysis and encouraging cell growth ( Christie, 2004 ). Dyella terrae strain Ely Copper Mine may have evolved these mechanisms as an adaptive response to predation pressure, enhancing its persistence ( Hoque et al, 2021 ). Other virulence genes were also found in the genome, including those encoding an ANK-containing protein, which has unclear origins but may be acquired from eukaryotes via horizontal gene transfer or result from convergent evolution ( Al-Khodor et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that nonsynonymous SNP (nsSNP) mutations in conserved regions of FlrA were detected duringc long-term coincubation with Acanthamoeba castellanii (A. castellanii), and during long-term intra-amoebal host adaptation of V. cholerae resulted in enhanced colonization in zebrafish [45]. All of the nsSNP of FlrA occurred in the central domain and one deletion occurred in the flanking region of the central domain and C-terminal HTH domain.…”
Section: Plos Pathogensmentioning
confidence: 99%